Speech Intelligibility Test for Polish Language – Relation to the Acoustic Properties of Classrooms and Comparison to Other Languages - Jan RADOSZ (Archives of Acoustics)
Numerous studies have shown that teachers often speak louder in classrooms because of the acoustic properties of the spaces. To improve the acoustics in classrooms, it is necessary to develop relevant acoustic criteria. Existing evaluation scales for parameters of room acoustics have been developed on the basis of studies of adults for a variety of languages (e.g. Dutch and English). One of the issues still not fully recognized is the effect of the respondents’ language and age on the results of speech intelligibility tests. The aim of the study was to recognize the possibility of applying some international guidelines for room acoustics developed on the basis of adult studies to classrooms in Polish schools. This paper presents a study of the speech intelligibility of Polish-speaking children (10–13 years old) in conjunction with parameters of room acoustics. It also compares studies of speech intelligibility for other languages. The study confirmed a relationship between the results of speech intelligibility tests and speech transmission index STI for classrooms with varied acoustics. It also showed that the results of Polish word test are similar to results of English tests (Anderson, Kalb, 1987; Jacob et al., 1990).